Conformational Studies on γ - Benzyl- L- Glutamate and L- Valine Containing Block Copolypeptides - Ajay Kumar (E-Journal of Chemistry)
Conformational studies on γ - benzyl-L- glutamate and L- valine containing block copolypeptides are reported using IR and CD spectra. The block copolypeptides contain valine block in the center and on both sides of the valine are γ - benzyl- L- glutamate blocks. The changes in conformation with increase in chain length of γ - benzyl- L- glutamate blocks are observed. When the chain length of γ - benzyl-L- glutamate block is 13, the block copolypeptide crystallized into beta conformation. With increase in chain length of γ - benzyl-L- glutamate block from 13 to 30 the conformation of the copolypeptide changes from beta sheet to alpha helix, but small amount of beta component also remains. With further increase in chain length of γ - benzyl- L- glutamate block from 30 to 45 the copolypeptide crystallizes exclusively into alpha helix conformation.